IMPLEMENTASI KEBIJAKAN KERINGANAN PAJAK KENDARAAN BERMOTOR PADA KANTOR DINAS PENDAPATAN DAERAH PROVINSI SULAWESI TENGAH - Alatas, Imran Wahyudy (Katalogis, 2015)
The purpose of this study was to determine the Implementation of Motor Vehicle Tax Relief Policy in the Office of Regional Revenue Office of Central Sulawesi Province. The main theory used in this study are those of Edward III on four factors influencing policy implementation is communication, resources, disposition and bureaucratic structure. This type of research uses a qualitative approach to survey techniques. Informants in this study of three people who choose with purposive sampling. The results showed the implementation of the Motor Vehicle Tax Relief Policy in the Office of Regional Revenue Office of Central Sulawesi Province which consists of four indicators of communication, resources, disposition and bureaucratic structure. Of the four sub indicators are still no indicators that still need to be improved, namely sub-indicators of physical facilities, the implementor of policies and attitudes that lead to policy-makers on the creation of good results.